Joint assessment in von Willebrand disease - van Galen, Karin P. M.; Timmer, Merel A.; de Kleijn, Piet; Fischer, Kathelijn; Foppen, Wouter; Schutgens, Roger E. G.; Eikenboom, Jeroen; Meijer, Karina; Cnossen, Marjon H.; Fijnvandraat, Karin; van der Bom, Johanna G.; Larosvan Gorkom, Britta A. P.; Leebeek, Frank W. G.; Mauser-Bunschoten, Eveline P.; on behalf of the Win study group (Thrombosis and Haemostasis, 2017)
Assessment of clinical outcome after joint bleeding is essential to identify joint damage and optimise treatment, to prevent disability. However, disease-specific tools to assess the musculoskeletal status in patients with von Willebrand disease (VWD) are lacking. We aimed to determine validity and reliability of the Haemophilia Joint Health Score (HJHS) and Haemophilia Activities List (HAL) in patients with Von Willebrand disease (VWD). Ninety-six patients with VWD were included (mean age 46 years) of whom 27 had more than five documented joint bleeds. The HJHS was performed in all patients and all patients completed the HAL and Impact on Participation and Autonomy (IPA) questionnaires. Health-related quality of life (SF36) results were obtained from the prior ‘Willebrand in the Netherlands’ study. Joint X-rays of knees, elbows and ankles were scored according to Pettersson (PS). Internal consistency of the HJHS (Cronbach’s α (α)=0.75) and HAL (α=0.89) were good. Inter-observer agreement of the HJHS was good (ICC 0.84; Limits of Agreement ± 10.3). The HJHS showed acceptable correlation with the X-ray PS (Spearman’s r (rs)>0.60 all joints) and HAL (rs=0.71). The HAL also showed acceptable correlation with the SF36 physical functioning (rs=0.65) and IPA (rs=0.69). Hypothesis testing showed adequate discriminative power of both instruments: in patients with a history of >5 versus ≤ 5 joint bleeds (median HJHS 10 vs 2 (p<0.01); median HAL 77 vs 98 (p<0.01)), independent from age. In conclusion, both the HJHS and HAL are feasible to assess clinical outcome after joint bleeds in VWD.
Keywords: HAL; HJHS; reliability; validity; VWD